Efficient Transmission of H.264 Video over Multirate IEEE 802.11e WLANs. (24th March 2008) - Pourmohammadi Fallah, Yaser; Nasiopoulos, Panos; Alnuweiri, Hussein
Abstract : The H.264 video encoding technology, which has emerged as one of the most promising compression standards, offers many new delivery-aware features such as data partitioning. Efficient transmission of H.264 video over any communication medium requires a great deal of coordination between different communication network layers. This paper considers the increasingly popular and widespread 802.11 Wireless Local Area Networks (WLANs) and studies different schemes for the delivery of the baseline and extended profiles of H.264 video over such networks. While the baseline profile produces data similar to conventional video technologies, the extended profile offers a partitioning feature that divides video data into three sets with different levels of importance. This allows for the use of service differentiation provided in the WLAN. This paper examines the video transmission performance of the existing contention-based solutions for 802.11e, and compares it to our proposed scheduled access mechanism. It is demonstrated that the scheduled access scheme outperforms contention-based prioritized services of the 802.11e standard. For partitioned video, it is shown that the overhead of partitioning is too high, and better results are achieved if some partitions are aggregated. The effect of link adaptation and multirate operation of the physical layer (PHY) is also investigated in this paper.